2019
DOI: 10.1002/elan.201800741
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐doped Hollow Co3O4 Nanofibers for both Solid‐state pH Sensing and Improved Non‐enzymatic Glucose Sensing

Abstract: Nitrogen‐doped hollow cobalt oxide nanofibers (Co3O4 NFs) with both glucose catalytic activity and pH sensitivity were fabricated through core‐sheath electrospinning technique, followed by calcination. The as‐developed nitrogen‐doped hollow Co3O4 NFs were thoroughly characterized using various techniques, and then employed to fabricate a dual electrochemical sensor for both pH sensing and glucose sensing. The pH sensitivity of the developed nitrogen‐doped hollow Co3O4 NFs demonstrated a Nernst constant of 12.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The diversity of the polar sites is beneficial for detecting charges produced in the electrocatalytic reaction [19]. It is found that the performance of non‐enzymatic glucose sensors can be tuned and enhanced efficiently by tailoring the nanostructures of Co 3 O 4 materials, including nanoparticles [20, 21], twin‐spheres [22], microspheres [23, 24], nanofibres [25, 26], nanowires [27, 28], nanorods [29, 30], nanosheets [1], nanoflowers [31], and so on. Among them, three‐dimensional (3D) hierarchical Co 3 O 4 nanoarchitectures are particularly interesting due to their excellent electrochemical performances, which result from their favourable specific surface area and stable 3D network.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of the polar sites is beneficial for detecting charges produced in the electrocatalytic reaction [19]. It is found that the performance of non‐enzymatic glucose sensors can be tuned and enhanced efficiently by tailoring the nanostructures of Co 3 O 4 materials, including nanoparticles [20, 21], twin‐spheres [22], microspheres [23, 24], nanofibres [25, 26], nanowires [27, 28], nanorods [29, 30], nanosheets [1], nanoflowers [31], and so on. Among them, three‐dimensional (3D) hierarchical Co 3 O 4 nanoarchitectures are particularly interesting due to their excellent electrochemical performances, which result from their favourable specific surface area and stable 3D network.…”
Section: Introductionmentioning
confidence: 99%
“…When used 2 mass.% Co 3 O 4 , maximum yields of vanillin were observed[70]. Dong et al explained that the catalytic property of the as-prepared Co 3 O 4 nanofibers towards glucose oxidation in alkaline solution is related to CoOOH and CoO 2 , which reversible reactions are described in research work[71].Liu et al[72] employed a one-pot hydrothermal method for the synthesis of flower-like Co 3 O 4 /graphitic carbon nitride (Co 3 O 4 /g-C 3 N 4 ) nanocomposite and its electrochemical behavior was investigated using cyclic voltammetry.…”
mentioning
confidence: 95%
“…Co 3 O 4 is a p-type antiferromagnetic oxide semiconductor with two band gaps and it is of great importance due to its optical, catalytic, and magnetic properties. The wide application areas of cobalt oxide nanostructures are known such as anode material in Li-ion rechargeable battery, catalyst, gas sensor, supercapacitor, electrochemical sensor, solar absorbing material, pH sensor, electrochromic devices, smart windows, photovoltaic devices, and magnetic materials [1][2][3][4][5][6][7][8][9][10][11]. Co 3 O 4 with a variety of morphologies such as wires, cubes, fibers, tubes, sheets, flowers, and hollow microspheres [12][13][14][15][16][17][18] have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Nonenzymatic glucose sensors are generally operated by a direct electrocatalytic oxidation of glucose at an electrode surface, which is modified with functional materials as a replacement of enzymes . Noble metals and alloy nanoparticles show high electrocatalytic activity toward glucose oxidation; however, they still suffer from sluggish kinetics and serious deactivation due to surface poisoning and fouling from intermediates or chloride ion adsorption. , Herein, versatile transition-metal oxides have been considered as one of the most promising catalysts for glucose detection, energy storage, and conversion, , owing to their low cost, good biocompatibility, and excellent electrocatalytic activity. These metal oxides that have been studied include MnO 2 , Co 3 O 4, NiO, , and CuO. Among these nonprecious metal oxide catalysts, MnO 2 has multiple crystallographic phases based on its tunnel structure, , which is recognized as an environmentally friendly electrocatalyst possessing high catalytic activity, good stability against corrosion, and abundant earth reserves. , The Co 3 O 4 -based nanocomposites enjoy outstanding electrocatalytic activity and stability because the cobalt ions possess d-band electrons exhibiting a similar property as the noble metals. , The diversiform d-orbitals in cobalt ions endow more dynamic d-electrons on the surface with highly active sites for electrocatalysis .…”
Section: Introductionmentioning
confidence: 99%
“…2 Noble metals and alloy nanoparticles show high electrocatalytic activity toward glucose oxidation; 1 however, they still suffer from sluggish kinetics and serious deactivation due to surface poisoning and fouling from intermediates or chloride ion adsorption. 3,4 Herein, versatile transition-metal oxides have been considered as one of the most promising catalysts for glucose detection, 5 energy storage, and conversion, 6,7 owing to their low cost, good biocompatibility, and excellent electrocatalytic activity. These metal oxides that have been studied include MnO 2 , 8−10 Co 3 O 4, 11−13 NiO, 14,15 and CuO.…”
Section: ■ Introductionmentioning
confidence: 99%